2012
DOI: 10.1002/jcp.24161
|View full text |Cite
|
Sign up to set email alerts
|

A network system for vitellogenin synthesis in the mussel Mytilus galloprovincialis (L.)

Abstract: The aim of this study is to assess, by RT-PCR, in situ hybridization, electron microscopy, and immunohistochemistry, the site/s of vitellogenin (VTG) synthesis in the mussel Mytilus galloprovincialis. Our investigations demonstrate that, among the analyzed tissues, the synthesis of VTG occurs only in the female gonad, that is, within the oocyte and follicle and connective cells. Such a synthesis is just evident in early vitellogenic oocytes, whose cytoplasm is characterized by numerous RER cisternae and an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…Later (Stages II), labeling was within ADGs and in the ovarian follicles (Figure e,f). In particular, inside follicles, labeling for ER1 (Figure e), ER2 (Figure f ) mRNA was detectable within oogonia (Figure f, inset) and in vitellogenic oocytes and in follicle cells (Figure e, inset), both engaged in vitellogenesis (Agnese, Prisco, et al, ; Agnese, Verderame, et al, ). In Stage III, when ADGs are lacking, labeling was also detectable and localized in full growth oocytes (Figure g,h) that are ready for spawning.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Later (Stages II), labeling was within ADGs and in the ovarian follicles (Figure e,f). In particular, inside follicles, labeling for ER1 (Figure e), ER2 (Figure f ) mRNA was detectable within oogonia (Figure f, inset) and in vitellogenic oocytes and in follicle cells (Figure e, inset), both engaged in vitellogenesis (Agnese, Prisco, et al, ; Agnese, Verderame, et al, ). In Stage III, when ADGs are lacking, labeling was also detectable and localized in full growth oocytes (Figure g,h) that are ready for spawning.…”
Section: Resultsmentioning
confidence: 97%
“…Differently, the levels of ER2 mRNA are always very high reaching a maximum in correspondence with vitellogenesis. It is interesting to note that in M. galloprovincialis , during the Stage II, the oocyte synthesize and accumulate the highest level of vitellogenin, whose production occurs also in ADGs and follicles cells (Agnese, Prisco, et al, ; Agnese, Verderame, et al, ), that is in different districts of the ovary where the presence of ERs also occurs. Moreover, treatments in vitro with 17β‐estradiol induce an increase of E2 mRNA in M. galloprovincialis (Nagasawa et al, ), and that in bivalves estrogens have been reported to induce the synthesis of vitellogenin which is the major event during gonadal development (Li, Osada, Suzuki, & Mori, ; Osada et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This protein is the main yolk protein in oocytes in this species [63,80], whereas vitellogenin (Vtg), the precursor of egg yolk proteins in many species of vertebrates and invertebrates [81], has never been reported in freshwater gastropods. Alterations of Vtg production were reported in male fish affected by intersex in field and laboratory studies [42,82,83].…”
Section: Discussionmentioning
confidence: 99%